Long‐term Outcomes of Vocal Fold Paralysis Following Patent Ductus Arteriosus Ligation in Neonates. (20th August 2022) - Orb, Quinn; Dunya, Gabriel; Padia, Reema; King, Jerald; Holbrook, John; Muntz, Harlan; Smith, Marshall E.
Abstract : Introduction: In patients undergoing patent ductus arteriosus (PDA) ligation there is a significant risk of left vocal fold paralysis (LVFP) particularly in premature neonates who are small for gestational age. The objective of this study is to determine the incidence of LVFP in infants following PDA ligation and report on long‐term outcomes in patients with LVFP. Methods: We performed a prospective study of patients undergoing PDA ligation in the newborn intensive care unit (NICU) between April 2004 and May 2014. Following PDA ligation, flexible laryngoscopy was performed to assess vocal fold mobility. Patients were then followed longitudinally to determine long‐term outcomes. Results: A total of 163 infants underwent PDA ligation. Thirty‐six patients (22%) developed LVFP following the procedure. Twenty‐five percent of neonates <1500 g experienced LVFP versus 5% of patients >1500 g ( p = 0.033). Patients with LVFP were more likely to require a feeding tube (64% vs. 19.6%; p < 0.05) and spent more time in the NICU (135 days vs. 106 days; p < 0.05). Twenty‐four patients received long‐term follow‐up. Six (25%) had complete resolution of LVFP, 10 (42%) were compensated, and 8 (33%) demonstrated persistent LVFP with no improvement. Conclusions: The incidence of LVFP after PDA ligation is high especially in extremely low birth weight children. The majority of patients recovered well with time, but further surgical intervention was required in uncompensated cases. Long‐term follow‐up of these patients is needed to ensure improvement. Laryngoscope, 133:1257–1261, 2023 Abstract : Premature infants undergoing patent ductus arteriosus ligation are at risk for vocal fold paralysis leading to long term voice and swallowing complications. In this study, we review risk factors for vocal fold paralysis and offer insight into long term outcomes and further treatment needs in this unique patient population.